The Effectiveness of Assertiveness Training on Anxiety Symptoms in School-Age Children With Specific Learning Disorder - Mehdi Mohagheghi; Masoumeh Pourmohamadreza-Tajrishi; Soheila Shahshahanipour; Gita Movallali; Mohsen Vahedi (Journal of Rehabilitation, 2021)
Objective: Specific learning disorder is a type of neurodevelopmental disorder, in which children with disabilities have difficulty understanding, or using spoken and written language. The disorder diagnoses when children have significant reading, writing, and math skills lower than expected. One of the characteristics of children with a learning disorder is the presence of anxiety symptoms, which are often chronic, and failure to address them can negatively affect the child's growth and academic performance. Assertiveness training is a structured intervention that uses to reduce the symptoms of anxiety. The present study aimed to determine the effectiveness of assertiveness training on anxiety symptoms of male school-age children with special learning disorders in Tehran City, Iran. Materials and Methods: The present study was a quasi-experimental research in which a pre-test in addition post-test design with a control group used along with a five weeks follow-up. The population included 8-11 year-old male children who were studying in the Learning Disorders Centers in Tehran City in the school year 2019-2020. The sample consisted of 130 male school-age children who were in convenient selected from the five educational districts (2, 13, 12, 18, and 15). At first, the Colored Progressive Matrices (CPM) assessed all subjects and 72 children who got a normal intelligence quotient (≥85) completed the Child Spence Anxiety Scale (SCAS-C). The studied sample was selected according to the formula for the determining the sample size and the probability of its drop-out (34 people). After scoring the SCAS-C, 45 children received a moderate anxiety (44-88 points). Thirty-four students (19, 10, and 5, respectively with dyslexia, dysgraphia, and dyscalculia) were randomly selected among them and matched based on their age, school grade and socio-economic status. They randomly assigned to the experimental and control group with mean and standard deviation of age 10.45±2.25 and 8.87±1.89 respectively. The experimental group divided into three subgroups (six people in two groups and five people in one) due to the efficacy of training in small groups and participated in 10 assertiveness training sessions (twice a week and 90 minutes for per session) while the control group received only the mainstream programs in the Learning Disorder Center. All subjects assessed by the SCAS-C at the end of the training sessions and five weeks follow-up. The obtained data from pre-test and post-test situations analyzed by using univariate and multivariate analysis of covariance. In addition, the data were analysed by the analysis of variance with repeated measure to determine the stability of the assertiveness training after the five weeks follow-up Results: The results of univariate and multivariate analysis of covariance showed that there was a significant difference between the mean scores of anxiety symptoms and its components in the experimental and control groups before and after the assertiveness training sessions (p<0.01). The results based on the eta quotient show that the values of 66%, 66%, 32%, 63%, 63%, 71%, and 73% respectively of the variance of total anxiety symptoms, generalized anxiety, obsessive-compulsive disorder, personal injury fears, social phobia, separation anxiety and panic disorder/agoraphobia in students with special learning disorder can be explained by participation in assertiveness training intervention. The results of analysis of variance with repeated measure showed that the effect of assertiveness training has only lasted on reduction of generalized anxiety, personal injury fears, anxiety phobia, and obsessive-compulsive disorder after five weeks follow-up. However, the effectiveness of the intervention program not found for the total anxiety symptoms, separation anxiety and panic/agoraphobia after follow-up study. Conclusion: The results indicate that the assertiveness training can reduce the symptoms of anxiety and its components in school-age male children with specific learning disorder. Therefore, we conclude that the design and implementation of similar training programs help students to strive to establish interpersonal relationships, reduce the frustration of academic failure, express their feelings, think of possible ways to deal with anxious situations, manage their negative behaviour, and be prepared to accept multiple roles in adulthood. Thus, by providing assertiveness training, maladaptive behaviors and mental health problems (especially anxiety symptoms) can be preventive in students with special learning disorder in addition to prevent ongoing problems in the fields of education and occupation.